COMPARATIVE ANALYSIS OF DETERMINING THE WATER QUALITY INDEX OF THE UPPER CITARUM BASIN USING THE NATIONAL SANITATION FOUNDATION WATER QUALITY INDEX (NSF WQI) METHOD, PRATI INDEX, AND DINIUS INDEX - Herlindya Putri, Shefira
The Upstream Citarum Watershed is the largest watershed in West Java Province which supports the activities and livelihoods of the surrounding community. Thus, the water quality of the Citarum River should continue to be considered by determining the water quality status using the water quality index. There are many methods of determining the water quality index that can be used, for example, the National Sanitation Foundation Water Quality Index (NSF WQI), the Prati Index, and the Dinius Index. This study aims to produce a comparison of the three methods based on secondary data in the form of water quality data from the Dinas Lingkungan Hidup (DLH) of West Java Province in 2013 – 2022 at four monitoring point such as Wangisagara, Koyod, Setelah IPAL Cisirung, and Nanjung as well as primary data in the form of sampling data in February and June at the same monitoring point. The data obtained is grouped into data for wet – dry months, wet – dry years, monitoring points, and monitoring years. The results showed that the Dinius index method tends to classify water BOD5ies into higher water quality classes. Lower water quality class results were obtained when applying NSF WQI. Then, the Prati index is a “stricter” method and gives the results of the lowest water quality class. While the results of research on primary data show that NSF WQI and Prati Index tend to classify water BOD5ies into better water quality classes than Dinius Index.